Concept of Brahman as Vijñāna in the Light of Veda(s) and Upaniṣad(s) (NBPA Journal for Arts, Humanities & Social Sciences, 2026)
This paper follows the Vedic perspective in order to delineate the concepts of Brahman and Vijñāna. Truth and oneness are the fundamental attributes of Brahman. The possibility of the falsity of Brahman cannot be applied to it due to its absolute and sublimated one-centred nature, as presented in the epitomes of non-duality. The paper is divided into four parts. Part one reassesses the oneness-nature of Brahman, the relationship between “Saṁbhūti” and “Asaṁbhūti,” and Prāṇa, drawing on the Veda(s) within the construction of Brahman as Vijñāna. Part two examines the differential meanings of the terms—Vijñātmā, Vijñāta, and Vijānāti—as mentioned in the Upaniṣad(s) in respect of Brahman as Vijñāna. The subsequent part examines the interrelation between Brahman and Vijñāna from both transcendental and empirical perspectives within the framework of Śankarāchārya's non-dualistic philosophy. Regarding the paradox, a legitimate question about the portrayal of Brahman is how it can be imposed and overcome. At the stage of the epilogue, a brief but significant conclusion will be presented.